Phase Transitions Among of Valsartan Polymorphs due to Grinding and Humidity Variations - Yoga Windhu Wardhana; Risanteni Riskasari; Fikri Alatas (Indonesian Journal of Pharmaceutics, 2021)
Phase transition between drugs with polymorphisms needs attention due to unconscious changes in quality. Valsartan (VAL) is a drug model with polymorphic events to be studied here. Two polymorphic forms were obtained from recrystallization with various organic solvents such as acetonitrile and n-butyl acetate.  With untreated materials (from the market) were used as a comparison in this study. The phase transition of each polymorph was studied through grinding and humidity variations (RH 75% and 98%) treatment. The polymorph characterization was observed by microscope light polarization (PLM), Fourier Transform Infrared (FTIR), and Powdered X-ray Diffractometer (PXRD). The transition among polymorphic VAL was monitored by PXRD. There were significant differences in morphology, IR spectra, and diffractograms pattern. Found that the untreated VAL was amorphous, whereas the others were in high crystallinity. The polymorph form from n-butyl acetate was a metastable one that transformed easier into stable crystalline (from acetonitrile) than another polymorph.Keywords : Valsartan, Phase transition, Polymorphism, Recrystallization